The Bear Grylls Adventure. Book 6, The Earthquake Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2020)
The sixth adventure in the fun new 12-book collectible series for young readers from survival expert and Chief Scout BEAR GRYLLS.